Whose Hunger? : Concepts of Famine, Practices of Aid - Edkins, Jenny (Book collections on Project MUSE., 2000)
"We see famine and look for the likely causes: poor food distribution, unstable regimes, caprices of weather. A technical problem, we tell ourselves, one that modern social and natural science will someday resolve. Jenny Edkins responds to the contrary: famine in the contemporary world is not the antithesis of modernity but its symptom. A critical investigation of hunger, famine, and aid practices in international politics, Whose Hunger? shows how modernity frames our understanding of famine--and, consequently, shapes our responses. Edkins examines Malthus and the origins of famine theory in notions of scarcity. Drawing on the work of Lacan, de Waal, Foucault, Zizek, and particularly Derrida, she considers Amartya Sen's entitlement approach, the Band Aid/Live Aid events, and food for work projects in Eritrea as examples of the technologization and repoliticization of famine. From the politics of famine to the practices of aid, from the theories of modernity to the complex emergencies of modern life, from the broad view to the telling detail, this searching book takes us closer to a clear understanding of some of the worst ravages of our time"--Provided by publisher